Contribuição das ações de educação corporativa na disseminação de uma cultura de responsabilidade ambiental - Tinoco, Felipe Ribeiro (2009)
Most people spend a considerable amount of their time in a corporate environment; therefore it is a natural consequence that education becomes also an important matter to business corporations. It is increasingly recognized that the modern state appears to have failed to provide Education to all members of society. This has led to increasing roles in education performed by non-government organizations (NGOs) and the private sector. Nowadays, not only have corporate education programs become essential for a business to accomplish its strategies but these programs also have filled some of the gaps of traditional education. At the same time, the modern corporation is under increasing pressure to respect and preserve the natural environment and to be sustainable. For this reason, there is a close relationship between the role business play in education and a growing public concern about the natural environment. This dissertation analyses how Senac an organization that presents itself as environmentally responsible and that has a structured corporate education program disseminates values and attitudes regarding environmental management within its human resources development strategies and process. After having described and evaluated the course on Environmental Education offered by Senac to its employees and after having applied the Collective Subject Speech methodology, this research findings show that (i) Senac formally communicates and disseminates its environmentally responsible culture to its employees; (ii) the course on Environmental Education has succeeded in drawing employee s attention to issues regarding the subject; (iii) employees are acting within their own communities to help develop them, encouraged by the course.